Interprofessional health education and its impact on integral healthcare. (30th September 2020) - Silva, C; Abreu, L; Santos, K; Santos, S; Figueiredo, A
Abstract: Background: Interprofessionality is a tool for optimizing the human resources available towards the consolidation of a resolutive healthcare. However, applying it is a challenge due to the fragmented training of health professionals. Objective: to describe the experience of planning and executing an interprofessional health education activity. Methods: An educational workshop was developed aiming at interprofessional health practice. A clinical case was distributed, which addressed the story of an elderly person who suffered a stroke and lived with the sequels of this episode in addition to emotional trauma from the experience. Each professional was asked to define a therapeutic proposal for the case and one of them was invited to present his proposal and complement it based on the suggestions of the other members. Results: the workshop enabled the perception that, in isolation, no profession would be able to fully contemplate the patient's needs. Therefore, it encouraged the use of integrated action between different professionals by demonstrating that punctual and disjointed actions would not be sufficient to act effectively in the care and needs related to the individual's health. Conclusions: the final product of this workshop resulted in a consistent activity contemplated by multiple perspectives, experiences and knowledges which would not be so successful if planned in isolation by a single professional group. Key messages: Due to its low cost, interprofessional action responds to the new health needs of contemporary times and its implementation is of great value in combating the fragmented trend in health training. The interprofessional view is a common ground to health not only where the study took place but worldwide, consolidating itself as a valuable asset to the construction of integral healthcare.